Communication: A Basic Skill of Medical Practice - Mathur, Girish (Bangladesh Journal of Medicine, 2023)
The doctor-patient relationship is central to the practice of medicine and is essential for the delivery of high-quality healthcare in the diagnosis and treatment of disease. There is utmost need for effective communication in medical practice. Communication is the key that unlocks a number of benefits. It leads to increased patient satisfaction, better understanding of the treatment, improved compliance, and overall better health. Therefore, clearer communication better understanding, and thus, better outcomes in the patients’ and attendants’ satisfaction. The need for communication with patients should be emphasized as it helps patients feel at ease, reduces their anxiety and builds their confidence, makes patients/clients feel valued, and reduces the chances of medical errors. Some of the key barriers to effective communication are such as personal barriers: negative attitude by doctors towards communication and giving it a low priority due to their concern primarily to treat illness rather than focus on patients’ other needs which may be psychological or related to social wellbeing. Human failings, such as tiredness and stress: A lack of inclination to communicate with patients. This can be due to lack of time, uncomfortable topics, lack of confidence and concerns relating to confidentiality. Inconsistency in providing information and giving conflicting information by different healthcare providers. Organizational barriers, lack of time, pressure of work being subjected to interruptions. If the complains are justified it is important that you apologize and ask the relatives what they would like to be done about it. Any problem that the family feels or experience should be actively identified and appropriate action should be taken to resolve them. If their demanding behavior continues, set the limit and you can tell them that you cannot do better than what is being done. If the relatives insist on continuing to disagree about the patient’s management, it may be necessary to call some senior doctor to try to explain and convince them. Imparting bad news is an emotional experience for the doctor as well as the patient and requires additional targeted strategies. When you speak to the patient they get the chance to clarify their doubts. Medical schools/ Colleges must be encouraged to provide the best possible communication skills training as part of the core undergraduate curriculum. This training should have set objectives and clear methods of assessment. More communication skills training programs should be developed at post graduate level. Doctors should use the appraisal process as a vehicle for discussing the success of communication skills training. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 178